Clinical usefulness of the measurement of serum fructosamine in childhood diabetes mellitus - Dong Soo Kang; Jiyun Park; Jae Kyung Kim; Jeesuk Yu (Korean Society of Pediatric Endocrinology, 2015)
PurposeGlycosylated hemoglobin (HbA1c) is often used as an indicator of glucose control. It usually reflects the average glucose levels over two to three months, and is correlated with the development of long-term diabetic complications. However, it can vary in cases of hemoglobinopathy or an altered red blood cell lifespan. The serum fructosamine levels reflect the mean glucose levels over two to three weeks. This study was designed to determine the clinical usefulness of the combined measurement of serum fructosamine and HbA1c in the management of childhood diabetes mellitus and the correlation between them.MethodsClinical data on 74 Korean children and adolescents with diabetes mellitus who were under management at the Department of Pediatrics of Dankook University Hospital were evaluated. Their fructosamine and HbA1c levels were reviewed based on clinical information, and analyzed using IBM SPSS Statistics ver. 21.ResultsTheir HbA1c levels showed a strong correlation with their fructosamine levels (r=0.868, P<0.001). The fructosamine level was useful for the prompt evaluation of the recent therapeutic efficacy after the change in therapeutic modality. It was also profitable in determining the initial therapeutics and for the estimation of the onset of the disease, such as fulminant diabetes.ConclusionThe measurement of both fructosamine and HbA1c was useful in managing childhood diabetes mellitus, especially when there was discrepancy between the clinical information and the HbA1c level.